Navigating the Perfect Storm: Ultrasound-Guided Peripheral Nerve Block for Emergency Amputation in a Patient with Acute STEMI and Failed PCI - Ella Priliandini; Ruddi Hartono; Ahmad Feza Fadhlurrahman; Muhammad Farlyzhar Yusuf (HM Publisher, 2025)
Acute limb ischemia presenting concurrently with acute coronary syndrome creates a precarious clinical dilemma, often termed the